OPTIMALISASI PEMBELAJARAN KELAS MELALUI PENANGANAN RASA KANTUK: ANALISIS FAKTOR DAN SOLUSI PRAKTIS UNTUK SISWA MENGANTUK DI MA MUHAMMADIYAH 2 PATEAN - Vivin Rahmawati; A. Kurniawan Pasmadi (As-Sulthan Journal of Education, 2025)
Every living creature feels sleepiness, students often feel sleepy when they are in the learning process. Students are often unfocused, lethargic, and not enthusiastic about the learning process, especially at certain times, such as learning that occurs before dhuhur time. This research aims to optimize the learning process, find out the factors that cause drowsiness that occur in students during learning, and appropriate solutions so that students do not feel sleepy in class. The approach used is qualitative with case study research methods, through data collection techniques using observation, interviews and documentation methods. The results and conclusions of the research show that the factors causing students' sleepiness during class are lack of sleep, lots of activities outside of learning hours, boredom felt by students, and lack of motivation from the teacher or from the students themselves. The solution to avoid students feeling sleepy during class is to improve the quality of sleep at night, increase interaction between teachers and students, improve the quality of learning by using appropriate learning methods, when the learning method is interesting for students, then students no longer feel sleepy, bored and lethargic in learning.